Implementation of Islamic Boarding School Cooperative Management in Forming the Entrepreneurial Spirit of Santri - Izzetillah, Iqvina; Ghafur, Abd; Arifin, Moh. Samsul (Jurnal Ilmiah Manajemen Kesatuan, 2024)
Islamic boarding schools have various functional units, apart from the existing Islamic boarding school education, there are business units called cooperation. The success of management in cooperation cannot be separated from the skills of the management elements in managing the cooperation. One aspect that needs to be considered is the formation of the entrepreneurial spirit of the students. This research aims to find out how the management of the Ainul Hasan Islamic boarding school cooperation (Koperasi Pondok Pesantren/Kopontren) is implemented, and to find out the role of the Ainul Hasan Islamic boarding school Cooperation (Kopontren) in forming the entrepreneurial spirit of students. The research method used is a qualitative method with a case study approach. Data were collected through interviews, observation and documentation with Islamic boarding school caregivers, Kopontren administrators, alumni and several students of the Ainul Hasan Islamic boarding school. The research results showed that the management of the Ainul Hasan Islamic boarding school cooperation (Kopontren) is quite good in implementing its management system because it is seen from the management function which really supports management activities so that the desired goals can be achieved well. The implementation of Ainul Hasan's Islamic boarding school cooperation management (Kopontren) in forming the entrepreneurial spirit of students is by holding entrepreneurship training for students to make brooches from flannel which is held once a week. By implementing good Islamic boarding school cooperation management and entrepreneurship training, students can form the entrepreneurial spirit and help students become successful entrepreneurs in the future.